Wykluczenie nierozerwalności małżeństwa i potomstwa przez pozwaną w świetle wyroku Roty Rzymskiej c. Monier z 6 marca 2015 roku - Góralski, Wojciech (Ius Matrimoniale, 2017)
The presented sentence of the Roman Rota, to which the author provides a comment, concerns nullitatis matrimonii, which was heard by the turnus c. Monier on the grounds of exclusion by the female defendant of the indissolubility of marriage and offspring. This sentence was passed by another instance, after obtaining by the male claimant nova proposition causae (in the first and third instance the sentence was negative, in the second instance it was positive); the defendant failed to attend all three instances. However, her testimony given in c. Monier instance, fully confirmed by the claimant and witnesses, unequivocally demonstrated that she simulated marriage consent – both in reference to bonum sacamenti and bonum prolis (the reason for both simulations were her beliefs concerning marriage and its procreative purpose, which deviated from the teaching of the Church). The sentence of the Roman Rota c. Monier is an example of an in-depth assessment of means of proof, which enabled to convincingly declare the nullity of marriage.